HUBUNGAN FPB DAN KPK DALAM BILANGAN BULAT - Hidayatin, Nur; Sulisawati, Dwi Noviani (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2024)
This research was a development of the theory of FPB and KPK with the aim of studying the relationship between FPB and KPK on integers referring to the concept of divisibility and focusing on the analysis of theorems related to the relationship between FPB and KPK along with their proofs to validate the truth of the theorem. The objects in this study are FPB and KPK in the scope of the integer number system. This type of research is qualitative research by conducting a literature review process on the concept of FPB and KPK and then developing it to produce a new theorem related to the relationship between FPB and KPK and then proving its truth. The results of this study obtained one theorem related to the relationship between FPB and KPK on integers so that it can add to the knowledge that can be used as additional material in learning Number Theory.